Acqua di mare e sale nei riti purificatori greci - Zaccagnino, Cristiana (O T I V M, 2017)
Water is the first element we think about when we want to purify something, someone, a place, or ourselves. Water played an important role also in the ancient Greek world. Saltwater, as well as salt on its own, seems to have been regarded as more effective than freshwater: Iphigenia affirms that ‘sea washes away all men’s evils’ (Euripides, Iphigeneia in Tauris, 1153). Because of its characteristics, the sea was considered a suitable medium for carrying out purification, ordeal, and punishment. In addition seawater seems to have a special relation with the sexual sphere, sometimes when taboos have been violated.